SELF-HEALING DALAM QS AL-INSYIRAH:: Analisis Penafsiran Hamka Dalam Tafsir Al-Azhar - Hazmi, M. Hafiz Mauluddin (Program Studi Ilmu Al-Quran dan Tafsir, 2025)
Generation Z faces significant mental health challenges, with the 2022 I-NAMHS report indicating that one in three adolescents in Indonesia experiences mental disorders, with 2.45 million facing severe issues. Factors such as excessive use of technology, high stress levels, inactive lifestyles, and social pressure are the primary triggers of this problem. One approach to addressing these issues is self-healing, a concept focused on an individual’s ability to calm the mind, restore energy, reduce stress, and enhance emotional balance. This study employs a library research method with a descriptive-analytical approach, deeply analyzing QS al-Insyirah through the tafsir tahlili method. Hamka’s Tafsir al-Azhar serves as the primary reference to connect the spiritual values of the Qur’an with the concept of self-healing. The results show that two main principles in the interpretation of QS al-Insyirah, namely wisdom and reliance on Allah (tawakkal), are relevant to modern self-healing. Wisdom helps individuals develop a healthy mindset to face difficulties with serenity and gratitude, while tawakal teaches acceptance and trust in Allah’s decisions after maximal effort. This study emphasizes that integrating Qur’anic values such as wisdom and tawakal with modern self-healing concepts offers a holistic approach to strengthening mental health. These findings not only enrich theoretical insights but also provide practical Islamic guidance to address stress, trauma, and emotional challenges in modern society.